Presenilin 2 overexpression is associated with apoptosis in Neuro2a cells - Kumar Ashish; Sivanandam T. M.; Thakur M. K. (Translational Neuroscience, 2016)
Presenilin 1 (PS1) and PS2 are evolutionarily conserved transmembrane proteins of the aspartyl protease family. Initially, they were reported to be associated with the early onset of familial, early-onset Alzheimer’s disease. PS1 has been implicated in several crucial brain functions including developmental processes, synaptic plasticity, and processing of various molecules, while PS2 has been poorly studied and is considered to be a compensatory partner of PS1. Certain controversial reports have suggested that PS2 has a role in apoptosis, though the underlying mechanism is not clear. To ascertain the role of PS2 in apoptosis, mouse neuroblastoma cells (Neuro2a) were transfected with a cDNA construct encoding full length mouse PS2 and analyzed for viability, expression of PS1, PS2, Bax and p53, Bax protein, and status of chromatin condensation. Our results showed reduced viability, condensed chromatin and higher expression of Bax at mRNA and protein levels, but no change in the expression of p53 and PS1 in PS2-overexpressing Neuro2a cells. Thus, it is evident that PS2, independent of PS1, is associated with apoptosis via a Bax-mediated pathway. These findings might help in the understanding of the involvement of PS2 in apoptosis and its associated brain disorders.